THE BEAUTIFUL - HARMONY BETWEEN IMAGINATION AND ORDER - Markova, Ilinida (E-Journal VFU, 2024)
Is the search for the idealistic justified in an age dominated by pragmatism, convenienceand consumption?! Does man find strength to contemplate the beautiful? How could it survivein such a hostile environment and is there any point to its existence? These and some other questions are attempted to be answered in this paper. Though they may sound remote to the “modern ear”, the fact that in all ages their answers have been given is telling enough - on the one hand, no definitive one has been found, and on the other, each answer reveals only afragment of the whole picture. Amidst all this chaos of contradictions and desires is the man, constantly fixated on his passions, looking with nostalgia at the horizon (past and future) and knowing he will not achieveit - a tragic hero in a tragic "game" - himself borderline in his suffering.
Keywords: soul; spirit; nature beautiful; cosmos; art; Beautiful